Influence of ball possession and playing position on the physical demands encountered during professional basketball games - Ferioli, Davide; Rampinini, Ermanno; Martin, Marco; Rucco, Diego; La Torre, Antonio; Petway, Adam; Scanlan, Aaron (Biology of Sport, 2020)
Understanding the game demands encountered in basketball provides useful insight for developing specific, individualized and team-based training sessions. This study quantified and compared the game activity demands encountered by basketball players of different playing positions: i) strictly when in possession of the ball and ii) overall during live playing time (irrespective of ball possession). The activity demands encountered by 44 (22 guards, 14 forwards, 8 centres) adult, professional, male basketball players were assessed across 10 official games. Time-motion analysis was used to determine the frequency and proportion (%) of playing time performing recovery (REC), low- (LIA), moderate- (MIA), and high- (HIA) intensity activities. Linear mixed models were constructed to examine differences in dependent variables between playing positions, accounting for repeated measures. Guards, forwards, and centres spent 11.9±5.9%, 3.5±1.3%, and 2.9±1.1% of live playing time in possession of the ball, respectively. Guards performed more activities at all intensities (total movements, REC, LIA, MIA, and HIA) than forwards (P < 0.05) and centres (P < 0.05) when in possession of the ball. The proportion of time spent performing HIA in possession of the ball was greater for forwards (P = 0.001) and centres (P = 0.001) than guards. During live playing time overall across games, centres performed more HIA per minute (P = 0.049) and spent a greater proportion of time performing HIA (P = 0.047) than guards. Activities performed when in possession of the ball and during live playing time across basketball games are affected by playing position. These data highlight the need to develop position-specific training drills, particularly with ball possession.